Content Analysis of Gender Representation in Jordanian English as a Foreign Language (EFL) Textbooks - Adnan Bataineh (Faculty of Education - Port Said University, 2014)
This study performed a content analysis of gender representation in nine Jordanian English as a Foreign Language (EFL) textbooks. The purpose of this study was to examine whether or not these textbooks offered equitable gender representation of males and females. To examine gender representation, the study investigated the presence of women and girls and gendered occupational roles implied by images, photographs, illustrations, pictures, and texts found in Jordanian EFL textbooks. The results showed that Jordanian EFL textbooks contained significant and substantial gender inequities. Quantitative and qualitative data showed that females' presence is superficial in comparison with males' presence. In other words, the number of females in images, photographs, pictures, and illustrations was lower than the number of males. Moreover, the study showed that images and texts covertly and overtly portrayed males as superior and females as inferior. Finally, traditional, stereotypical, and biased images and perceptions of gender inequity still exist in these textbooks. In sum, the Jordanian EFL textbooks did not offer equitable representation of males and females.